Implementación de la herramienta de gestión balanced scorecard a una empresa de servicios de remolque, salvamento y asistencia a naves en los puertos del Ecuador - Pérez-Llona Salazar, Andrés Raúl (2009)
The globalization demands and obligates that the Ecuadorian companies tecnificate and evolutionate very fast to became a world class company, for this reason it has become a necessity the implementation of management systems .The following thesis is about the implementation of a strategic management system in a port operator whose main activity is to give the service of tow, rescue and assistance to ships in the terminals ands ports of Ecuador. The main problems that face this company are lack of a corporative strategy clearly identified and lack of measure of strategic performance. These problems affect the efficiency and quality of the company. The purpose of this thesis is to design a strategic map and a balance scorecard aligned to the goals and objectives of the company to orientate the efforts .The expected results of the implementation are: a clearly view strategy, identified goals, slim structure costs, large portfolio of costumers and to be recognized in the market.